B-doped graphene quantum dots implanted into bimetallic organic framework as a highly active and robust cathodic catalyst in the microbial fuel cell. (January 2022) - Yan, Yimin; Hou, Yanping; Yu, Zebin; Tu, Lingli; Qin, Shanming; Lan, Danquan; Chen, Shuo; Sun, Jiangli; Wang, Shuangfei
Abstract: Developing efficient and durable oxygen reduction reaction (ORR) cathodic catalysts plays an essential role in application of microbial fuel cells (MFCs). Herein, the B-doped graphene quantum dots implanted into bimetallic organic framework (BGQDs/MOF-t) are fabricated by a facile electro-deposition. Results show that, the in-situ growth of FeCoMOF on nickel foam can effectively assist construction of nanoflowers with compact connections, thus improves the conductivity. More importantly, this nano-network can serve as the template for the implantation of BGQDs through powerful interface of M-O-C bonding, avoiding π-π rearrangement and providing efficient charge transfer and abundant edge active sites. Benefitting from the enhanced electrode/electrolyte transport interface, abundant catalytic sites and low charge transfer resistance, the BGQDs/MOF-15 exhibits excellent ORR activity, superior to commercial Pt/C catalyst. In the MFC with the BGQDs/MOF-15 cathode, the maximum power density of 703.55 mW m −2 is achieved, which is 1.53 times of that of the Pt/C cathode. In addition, the BGQDs/MOF-15 cathode maintains great stability over 800 h, while that of Pt/C reduces to 61% of the initial voltage. This work opens new opportunities for developing efficient and durable MOF-derived ORR catalyst. Graphical abstract: Image 1 Highlights: BGQDs was implanted into FeCoMOF through the facile electro-deposition. FeCoMOF synergy with BGQDs to provide efficient charge transfer and abundant sites. The strong covalent bond M-O-C avoiding π-π rearrangement and improved stability. The BGQDs/MOF-t exhibited much higher power density than that of Pt/C in the MFC.